Carboxylate free μ-oxo bridged ferric wheel with a record exchange coupling. Issue 43 (19th October 2015) - Ahmed, Naushad; Upadhyay, Apoorva; Rajeshkumar, Thayalan; Vaidya, Shefali; Schnack, Jürgen; Rajaraman, Gopalan; Shanmugam, Maheswaran
Abstract : An oxo-bridged, carboxylate free 'ferric wheel' was isolated with the molecular formula [FeIII8(μ-O)4 (L 2− )8 ] (1 ). The strength of antiferromagnetic interaction between the Fe(iii ) ions is revealed by magnetic simulation ( J 1 = −26.4 and J 2 = −170 cm −1 ). The exchange value of −170 cm −1 is the largest exchange value known for any homometallic or heterometallic wheels reported to date. Abstract : A novel oxo-bridged, carboxylate free 'ferric wheel' was isolated with the molecular formula [FeIII8(μ-O)4 (L 2− )8 ] (1 ). Magnetic susceptibility measurements suggest that the Fe(iii ) ions are coupled antiferromagnetically and magnetic data modelling yields J 1 = −26.4 cm −1, J 2 = −170 cm −1 which are rationalized by DFT calculation. The exchange value for1 of −170 cm −1 (Fe–O(oxo)–Fe) is the largest exchange value known compared to any homometallic or heterometallic wheel reported to date.